Characterization of Fatty Acid EXporters involved in fatty acid transport for oil accumulation in the green alga Chlamydomonas reinhardtii - Nannan Li; Yan Zhang; Hongjun Meng; Shengting Li; Shufeng Wang; Zhongchun Xiao; Peng Chang; Xiaohui Zhang; Qing Li; Liang Guo; Yasuo Igarashi; Feng Luo (Biotechnology for Biofuels, 2019)
Abstract Background In the past few decades, microalgae biofuel has become one of the most interesting sources of renewable energy. However, the higher cost of microalgae biofuel compared to that of petroleum prevented microalgae biofuel production. Therefore, the research on increasing lipid productivity from microalgae becomes more important. The lipid production source, triacylglycerol biosynthesis in microalgae requires short chain fatty acids as substrates, which are synthesized in chloroplasts. However, the transport mechanism of fatty acids from microalgae chloroplasts to cytosol remains unknown. Results cDNAs from two homologs of the Arabidopsis fatty acid exporter 1 (FAX1) were cloned from Chlamydomonas reinhardtii and were named crfax1 and crfax2. Both CrFAXs were involved in fatty acid transport, and their substrates were mainly C16 and C18 fatty acids. Overexpression of both CrFAXs increased the accumulation of the total lipid content in algae cells, and the fatty acid compositions were changed under normal TAP or nitrogen deprivation conditions. Overexpression of both CrFAXs also increased the chlorophyll content. The MGDG content was decreased but the TAG, DAG, DGDG and other lipid contents were increased in CrFAXs overexpression strains. Conclusion These results reveal that CrFAX1 and CrFAX2 were involved in mediating fatty acid export for lipids biosynthesis in C. reinhardtii. In addition, overexpression of both CrFAXs obviously increased the intracellular lipid content, especially the triacylglycerol content in microalgae, which provides a potential technology for the production of more biofuels using microalgae.